Quality of care for patients evaluated for tuberculosis in the context of Xpert MTB/RIF scale-up. (May 2019) - Farr, Katherine; Nalugwa, Talemwa; Ojok, Christopher; Nantale, Mariam; Nabwire, Sarah; Oyuku, Denis; Shete, Priya B.; Han, Alvina H.; Fielding, Katherine; Joloba, Moses; Mugabe, Frank; Dowdy, David W.; et al.
Abstract: Rationale: Many high-burden countries are scaling-up Xpert MTB/RIF using a hub-and-spoke model. We evaluated the quality of care for patients undergoing TB evaluation at microscopy centers (spokes) linked to Xpert testing sites (hubs) in Uganda. Objectives: To characterize the extent to which patients were receiving care in accordance with international and national guidelines. Methods: We conducted a prospective cohort study of all adults with presumptive pulmonary TB at 24 health centers linked to Xpert testing sites. Health center staff photographed TB registers, and uploaded photos to a secure server bi-weekly. We assessed the proportion of patients (1) initiating testing; (2) completing testing; and (3) treated for confirmed TB within 14 days. Measurements and Main Results: Between January to December 2017, 6744 patients underwent evaluation for pulmonary TB. Only 1316 patients had sputum referred for Xpert testing, including 1075/3229 (33.3%) people living with HIV and 241/3515 (6.9%) without HIV. Of 119 patients confirmed to have TB by Xpert testing, 44 (36%) did not initiate treatment. There were significant losses along the entire diagnostic cascade of care, with only 5330/6744 (79.0%) patients having samples referred for sputum-based testing, 2978/5330 (55.9%) patients completing recommended testing if referred, and 313/418 (74.9%) patients initiating treatment within 14 days if confirmed to have TB. Conclusions: Although coverage of Xpert testing services across Uganda is high, the quality of care delivered to patients undergoing TB evaluation remains poor. Further research is needed to identify health system interventions to facilitate uptake of Xpert testing and high-quality care.